PENGARUH FAKTOR-FAKTOR ANTESEDEN E-CUSTOMER - Petra Surya Mega Wijaya; Ety Istriani (Jurnal Manajemen., 2015)
This study tries to combine research conducted by Wang and Yang (2008), Eid (2011) and Campbell (2013). Formulation of research problems are: (1) whether the e-customer loyalty is influenced by the e-customer satisfaction, customere-trust, and compulsive buying, and (2) whether the e-customer satisfaction and customer trusteinfluenced user interface quality, information quality, perceived security, perceived privacy, and competent behavior. A total of 200 questionnaires were distributed to the people of Yogyakarta purposive lyaged 15 years to 30 year sand never done an online transaction at least oncein thelast 6 months. Hypothesis testing using analytical tools. Structural Equation Modeling (SEM). The study states that all proposed hypothesis can be supported, so itcanbe concluded that (1) e-customer loyalty is influenced by the ecustomer satisfaction, customere-trust, and compulsive buying, and (2) the e-customer satisfaction ande-customer trustis influencedbythe user interfacequality, information quality, perceived security, perceived privacy, andcompetentbehavior.